THE POTENTIAL USE OF COMPUTERS IN ONLINE LEARNING IN THE DIGITAL ERA - Alim Hardiansyah; Sudianto (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
The development of digital technology has opened up great opportunities for the use of computers in online learning. In this digital era, computer becomes a very important tool in supporting distance teaching and learning process. The use of computers in online learning allows wider access to education, increases learning flexibility, and provides a variety of rich learning resources. Through various applications and learning platforms, students can interact with the subject matter more dynamically and interestingly. However, the use of computers in online learning also presents challenges such as the need for adequate infrastructure and improved digital skills for teachers and students. Nonetheless, the potential of computers in supporting online learning is huge and can bring positive changes in education in this digital era.